Opportunities for STEM-based Learning Models in Elementary Schools - Rima Yunika Pratiwi; Budi Rachman (Journal on Smart Learning Technologies, 2025)
Enhancing STEM literacy in elementary education is becoming increasingly imperative to address global challenges and technology advancements that require critical, creative, and collaborative thinking skills from a young age. The theme and project-based learning (PjBL) approach employed in elementary classrooms demonstrates promise for the integration of STEM elements. Nevertheless, educators' comprehension of this methodology is constrained, and institutional support is suboptimal. This study seeks to examine the perspectives of educators and administrators concerning the opportunities for applying STEM-based learning models in primary schools, while also identifying existing educational practices that may facilitate STEM integration. The research employed an exploratory qualitative methodology, utilizing in-depth interviews and participant observation across various public and private primary schools. The findings indicate that educators possess favorable views of the STEM methodology and have adopted thematic learning approaches that implicitly incorporate STEM components, albeit in an unstructured manner. The primary supporting variables consist of teacher inventiveness and student excitement, whereas the principal impediments are inadequate training, facilities, and curriculum guidelines. The findings underscore the necessity of creating a contextual, adaptable STEM paradigm tailored to the peculiarities of elementary school kids, supported by teacher training and collaboration among educational partners.